Dietary creatine supplementation does not affect some haematological indices, or indices of muscle damage and hepatic and renal function. Issue 4 (1st August 2000) - Robinson, Tristan M; Sewell, Dean A; Casey, Anna; Steenge, Gery; Greenhaff, Paul L
Abstract : Background —The use of creatine (Cr) as a nutritional supplement to aid athletic performance has gained widespread popularity among athletes. However, concerns have recently been expressed over potentially harmful effects of short and long term Cr supplementation on health. Methods —Forty eight young healthy subjects were randomly allocated to three experimental protocols aimed at elucidating any potential health risks associated with five days (20 g/day) to nine weeks (3 g/day) of Cr supplementation. Venous blood samples were collected before and after periods of Cr supplementation and were analysed for some haematological indices, and for indices of hepatic, muscular, and renal dysfunction. Findings —All measured indices were well within their respective normal range at all times. Serum creatinine concentration tended to be increased the day after Cr supplementation. However, values had returned to baseline six weeks after the cessation of supplementation. These increases were probably attributable to increased creatinine production rather than renal dysfunction. No indication of impairment to the haematological indices measured, hepatic function, or muscle damage was apparent after Cr supplementation. Interpretation —These data provide evidence that there are no obvious adverse effects of acute or more chronic Cr supplementation on the haematological indices measured, nor on hepatic, muscle, and renal function. Therefore there is no apparent health risk associated with Cr supplementation to healthy people when it is ingested in quantities that have been scientifically proven to increase muscle Cr stores.